A Modified Suction-Controlled Triaxial Equipment - Al-Sharrad, Muayad A.; Al-Ani, Salem M.; Zedan, Adnan J. (Nahrain University College of Engineering Journal, 2017)
The paper presents a modified equipment for triaxial testing of soil samples under unsaturated as well as saturated conditions. The equipment is capable of performing various types of hydro-mechanical loading including wetting and drying stress paths under constant or varying net stresses. The suction is controlled/ measured by using axis translation technique. Initial investigation on the performance of the testing system after appropriate calibrations had been conducted indicated good level of accuracy in measuring various soil properties